The Role Of Character Education In Elementary School Students In The Digital Age - Ahmad Riady Hasibuan; Maulyda Syita Ritonga (EDUCATION JOURNAL OF INDONESIA, 2024)
Character education is an attempt to apply religious, moral, and ethical values to students through knowledge, with the help of parents, teachers, and society. This is very important for the formation and development of student character. Every child has tremendous potential from birth, but that potential must be continuously honed and socialized in order for their character to be fully formed and developed. In today's all-digital era, children easily use digital media. Since there are many negative benefits and effects of this technology, educators, parents, and adults should help children understand and monitor what they are doing with digital media to ensure that they are using it at their best. This is inseparable from the fact that education always shapes and leads a person's life. Education both in schools, families, and community environments affects the formation of student character.   Keyword : Character Education, Primary school, Digital.